DNA polymorphism in strains of the genus Brucella. - Allardet-Servent, A (1988)
Preparations of DNA from 23 Brucella strains including 19 reference strains were compared by restriction endonuclease analysis. Pulsed-field gel electrophoresis resulted in optimal resolution of fragments generated by digestion with low-cleavage-frequency restriction enzymes such as XbaI. By this technique, five electrophoretypes were distinguished in five reference strains of the different species, i.e., B. abortus, B. melitensis, B. suis, B. canis, and B. ovis. Minor profile differences allowed us to discriminate between most biovars within a species. However, the differences in the DNA patterns of different field strains of biovar 2 of B. melitensis were not sufficient to serve as markers for epidemiological studies. From the XbaI fragments, we were able to estimate the size of the genomes of B. abortus 544T and B. melitensis 16 MT. This method revealed a relationship between DNA fingerprints, species, and pathovars which could shed light on problems concerning the classification and evolution of members of the genus Brucella.